The Dilemma of Administrative Sanctions in Legalizing Palm Oil Plantations in Indonesian Forest Areas - Maskun, Maskun; Violetta, Kiky Venna; Mukhlis, Muhammad Mutawalli; Normiati, Normiati; Tajuddin, Muhammad Saleh (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
Indonesia’s shift from criminal to administrative sanctions in addressing illegal use of forest areas—stipulated under Articles 110A and 110B of Law No. 6 of 2023—aims to legalize approximately 3.3 million hectares of unlicensed oil palm plantations. This study evaluates the effectiveness of administrative sanctions in promoting legal compliance and environmental accountability. Employing a normative legal research method with a descriptive qualitative approach, the study examines statutory frameworks, case studies, and empirical data from the Ministry of Environment and Forestry (MoEF). Findings reveal that while administrative sanctions offer expedited enforcement and reduce judicial burdens, they risk becoming legal loopholes exploited by corporations. The limited number of sanctioned companies—only 49—and the total fines of IDR 175.5 billion are disproportionately low relative to the scale of ecological damage. Nevertheless, the research highlights the potential of a hybrid enforcement model—integrating administrative, criminal, and civil legal instruments—to enhance compliance and ecological justice. It underscores the urgency of robust oversight and the application of criminal sanctions in severe cases to uphold the constitutional right to a healthy environment.